2011
DOI: 10.1152/ajpheart.00772.2010
|View full text |Cite
|
Sign up to set email alerts
|

Lack of microsomal prostaglandin E synthase-1 reduces cardiac function following angiotensin II infusion

Abstract: Harding P, Yang XP, He Q, LaPointe MC. Lack of microsomal prostaglandin E synthase-1 reduces cardiac function following angiotensin II infusion. Am J Physiol Heart Circ Physiol 300: H1053-H1061, 2011. First published December 30, 2010 doi:10.1152/ajpheart.00772.2010.-Our laboratory previously reported that inducible PGE2 synthase, mPGES-1, contributes to micromolar production of PGE2 in neonatal ventricular myocytes in vitro, which stimulates their growth. We therefore hypothesized that mPGES-1 contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…Previous studies have shown that C57BL/6 mice infused with ANG II show either normal (10,12,49) or only minimal impairment in LV systolic function (53) and do not demonstrate HF. In the present study, by adding both high salt intake and unilateral nephrectomy to ANG II infusion, cardiac function of ANS mice was significantly impaired, and mice devel- Results are means Ϯ SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that C57BL/6 mice infused with ANG II show either normal (10,12,49) or only minimal impairment in LV systolic function (53) and do not demonstrate HF. In the present study, by adding both high salt intake and unilateral nephrectomy to ANG II infusion, cardiac function of ANS mice was significantly impaired, and mice devel- Results are means Ϯ SD.…”
Section: Discussionmentioning
confidence: 99%
“…The C57BL/6 mouse strain serves as the genetic background of many transgenic and gene knockout models to validate the function of specific genes. Previous studies (10,12,49) have shown that ANG II infusion mouse models develop HHD with cardiac hypertrophy and fibrosis, but C57BL/6 mice infused with high doses of ANG II maintain cardiac function and do not develop HF (10,12,49). The transverse aortic constriction (TAC) model has been used for a mouse model of pressure overload (26), but it does not entirely mimic human HHD, and it is also difficult to prepare the model because microsurgical skills are required.…”
mentioning
confidence: 99%
“…7 However, another study using the same C57 background observes no impact of mPGES-1 deletion on the blood pressure (BP) response. 10 Facemire et al generated mPGES-1 −/− mice on two inbred backgrounds, DBA/1lacJ and 129/SvEv. 11 On the 129 background, BP was significantly higher in mPGES-1 −/− mice than wild type controls at baseline and also during Ang II infusion.…”
Section: State Of the Artmentioning
confidence: 99%
“…We and others have reported that deletion of mPGES-1fails to elevate blood pressure in mice fed either a normal or high salt diet (Cheng et al 2006; Francois et al 2007). Hypertension induced by infusion of angiotensin II in hyperlipidemic mice is also uninfluenced by mPGES-1 deletion(Harding et al 2011; Wang et al 2008). In contrast to these observations, Jia et al reported that mPGES-1 deletion augmented the hypertensive response to both a more intensive salt loading regimen and to angiotensin II infusion in normolipidemic mice (Jia et al 2006).…”
Section: Cardiovascular Consequences Of Mpges-1 Deletionmentioning
confidence: 99%
“…This adverse LV remodeling contrasts with the favorable PGI 2 dependent vascular remodeling in mPGES-1 knockout mice and is due to suppression of PGE 2 formation by inflammatory cells in the infarct and peri-infarct regions(Degousee et al 2008). Others reported that depletion of mPGES-1 impairs the compensatory hypertrophic response to prolonged angiotensin II infusion and reduces the ejection fraction (Harding et al 2011). These studies raise the possibility of adverse cardiac effects of mPGES-1 inhibitors in patients who had recently suffered a myocardial infarction or exhibit cardiac decompensation.…”
Section: Cardiovascular Consequences Of Mpges-1 Deletionmentioning
confidence: 99%